2020
DOI: 10.1016/j.jsxm.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Trajectories of Anal Intercourse Practice Over the Life Course Among US Women at Risk of HIV

Abstract: Introduction: Condomless anal intercourse (AI) confers a far greater likelihood of HIV transmission than condomless vaginal intercourse (VI). However, little is known about AI practice over the life course of women, to what extent AI practice is condom-protected, and whether it is associated with other HIV risk behaviors. We aim to describe longitudinal AI practice among HIV-seronegative women and to identify subgroups with distinct trajectories of AI practice. Methods: Using data from the Women's Interagency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The associations of AI which we identi ed here are similar to ndings of other papers, including to our previous analysis which used group-based trajectory modelling to identify groups with distinct AI behaviors among WIHS participants living without HIV (34). We found that the trajectory group reporting AI most consistently over the life course were, at baseline, more likely to identify as bisexual or lesbian, to report more male sex partners, and to report ever having experienced physical or sexual violence, compared to the group who rarely or never reported AI.…”
Section: Discussionsupporting
confidence: 84%
“…The associations of AI which we identi ed here are similar to ndings of other papers, including to our previous analysis which used group-based trajectory modelling to identify groups with distinct AI behaviors among WIHS participants living without HIV (34). We found that the trajectory group reporting AI most consistently over the life course were, at baseline, more likely to identify as bisexual or lesbian, to report more male sex partners, and to report ever having experienced physical or sexual violence, compared to the group who rarely or never reported AI.…”
Section: Discussionsupporting
confidence: 84%
“…Twenty‐six of the studies examined the prevalence and incidence of HSAI (Aral et al, 2005; Baldwin & Baldwin, 2000; Bazan et al, 2015; Brody & Potterat, 2003; Erickson et al, 1995; Friedman et al, 2001; Gindi et al, 2008; Gorbach et al, 2009; Gross et al, 2000; Halperin, 1999; Halpern & Haydon, 2012; Hess et al, 2016; Houston et al, 2007; Javanbakht et al, 2010; Leichliter et al, 2007; Mackesy‐Amiti et al, 2010; McBride & Fortenberry, 2010; Owen et al, 2020; Reynolds et al, 2010; Satterwhite et al, 2007; Scheidell et al, 2020). Prevalence of HS reporting recent AI ranged from 10% in Halpern and Haydon (2012) to 38% in McBride and Fortenberry (2010).…”
Section: Resultsmentioning
confidence: 99%
“…These included failure to use condoms at last coitus, reporting a younger age at first vaginal intercourse (VI), use of less reliable contraception (Baldwin & Baldwin, 2000); and use of recreational drugs or alcohol (Erickson et al, 1995; Friedman et al, 2001; Mackesy‐Amiti et al, 2010; McBride & Fortenberry, 2010; Reynolds et al, 2010). HS reporting AI were also more likely to be of White race; have non‐monogamous sex partners; a higher lifetime number of sex partners (Leichliter et al, 2007; Owen et al, 2020); and were more likely to have experienced violence or childhood trauma (Scheidell et al, 2020). Other studies noted that AI was more likely to be associated with the exchange of sex for drugs or money (Gorbach et al, 2009; Hess et al, 2016; Javanbakht et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The associations of AI which we identified here are similar to findings of other papers, including to our The number of missing values is high because in the first recruitment wave, women reporting no sex partners in the past 6 months were not asked whether they had ever practiced AI. In subsequent waves, all women were asked whether they had ever practiced AI previous analysis which used group-based trajectory modelling to identify groups with distinct AI behaviors among WIHS participants living without HIV [35]. We found that the trajectory group reporting AI most consistently over the life course were, at baseline, more likely to identify as bisexual or lesbian, to report more male sex partners, and to report ever having experienced physical or sexual violence, compared to the group who rarely or never reported AI.…”
Section: Discussionmentioning
confidence: 99%